2022
DOI: 10.1101/2022.12.30.521597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interplay of EXO70 and MLO proteins modulates trichome cell wall composition and powdery mildew susceptibility

Abstract: EXO70 proteins are essential constituents of the octameric exocyst complex implicated in vesicle tethering during exocytosis, while MLO proteins are plant-specific calcium channels of which some isoforms play a key role during fungal powdery mildew pathogenesis. We here detected by a variety of histochemical staining procedures an unexpected phenotypic overlap ofA. thaliana exo70H4andmlo2 mlo6 mlo12triple mutant plants regarding the biogenesis of leaf trichome secondary cell walls. Biochemical and Fourier tran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 92 publications
(190 reference statements)
0
3
0
Order By: Relevance
“…2021) cyclic nucleotide gated channels (CGNCs; Meng et al . 2020) and exocyst EXO70 subunits (Huebbers et al . 2022), no other plant proteins have been reported to date to associate in planta with MLO proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2021) cyclic nucleotide gated channels (CGNCs; Meng et al . 2020) and exocyst EXO70 subunits (Huebbers et al . 2022), no other plant proteins have been reported to date to associate in planta with MLO proteins.…”
Section: Discussionmentioning
confidence: 99%
“…While this approach was used in the context of the present work to probe the MLO2-CAM2 interaction, it could be deployed in future studies to identify novel interaction partners of MLO proteins. Apart from CAM (Kim et al 2002a;Kim et al 2002b;Kim et al 2014;Zhu et al 2021) cyclic nucleotide gated channels (CGNCs; Meng et al 2020) and exocyst EXO70 subunits (Huebbers et al 2022), no other plant proteins have been reported to date to associate in planta with MLO proteins.…”
Section: Discussionmentioning
confidence: 99%
“…While this approach was used in the context of the present work to probe the MLO2–CAM2 interaction, it could be deployed in future studies to identify novel interaction partners of MLO proteins. Apart from CAM [ 22 , 23 , 26 , 24 ], cyclic nucleotide gated channels (CGNCs; [ 14 ]) and exocyst EXO70 subunits [ 46 ], no other plant proteins have been reported to date to associate in planta with MLO proteins. Being integral membrane proteins, the identification of protein interaction partners is notoriously difficult for MLO proteins.…”
Section: Discussionmentioning
confidence: 99%